Análise do desempenho de sistemas fotovoltaicos aplicados à edificação - Siluk, Andrei Ruppenthal (2017)
The use of renewable energy boosts economic growth combined with sustainable development. Photovoltaic solar energy generated from solar radiation is a renewable source that contributes to this. The building applied photovoltaic systems that are integrated to the network represent and advantage in relation to the generation at a powerplant, since they avoid losses in the transmission and distribution system. to the building and integrated to the network represent an advantage in relation to the generation in plants, since they avoid losses in the transmission and distribution system. Furthermore, they do not require additional free area, as they are applied to the roofs of existing buildings, often as renovation. Regarding this technology, several factors are of influence on its performance, such as geographic location, solar orientation, operating temperature of the photovoltaic module, among others. Studies carried out in other countries indicate that the distance of the photovoltaic module in relation to the roof of the building influences its operational efficiency. This is because, the photovoltaic system located at the city of Santa Maria - RS. Information was collected in the period between January 2015 and December 2016 aiming at the analysis of the capacity for electric power generation in the weather conditions of this period. This information allowed a performance assessment of the system and its comparison with other systems located in other regions of the country. Specific ranges of temperature and irradiation data were also analyzed to find a relation with the performance of the system. As a result, it was observed that the increase in the ambient temperature, and the consequent increase of the module temperature, probably due to high irradiation ranges, tend to decrease the performance of the photovoltaic system in consonance with the results of other works. It is emphasized that also factors other than temperature, such as dirt observed in the studied PV modules can influence the performance ratio. The existing quantities of the studied system were calculated and compared with other systems installed in other regions of Brazil. It was verified that the studied system, despite the architectural and operational conditions in which it is, reflected a proper operation.